History of Biblical Israel : major problems and minor issues - Malamat, Abraham (Culture and history of the ancient Near East, 2001)
This title encompasses the history of Israel from its very beginnings up to the destruction of the First Temple of Jerusalem in 586 BC. Topics covered include: the Exodus and the conquest of Canaan; the rise of the Davidic Dynasty; and the diplomatic, international marriages of Solomon.